PENINGKATAN PRESTASI BELAJAR MATEMATIKA PECAHAN SEDERHANA DENGAN MENGGUNAKAN PENDEKATAN REALISTIK PADA SISWA KELAS III MI RIYADLUL ULUM BANGIL - Nanda septiana (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
The success of a teaching and learning process in the realm of education in schools is heavily influenced by several determinants. The factors in question are for example teachers, students, curriculum, social environment, and others. From the several findings found by the author in the teaching and learning process in the classroom, especially in fractional material, the learning outcomes of students are not good, where the results are quite low. This happens a lot to grade III MI Riyadlul Ulum Bangil, where there are students who find it difficult to understand how to solve simple fraction assignments. The type of research used in this research is Classroom Action Research (CAR), where the improvement of this research is through a cycle of two cycles. Based on the implementation of classroom action research in class III, MI Riyadlul Ulum Bangil can be concluded that using a realistic approach can increase the level of interest in student learning in the implementation of learning that is more lively and students are more active. From the results of class action in cycle I, there were criteria for increasing success in cycle I, a score of less than 70 or incomplete, there were 6 students (35%) and those who scored above 70 or said to have completed, there were 13 students (65%). However, after taking action in cycle II in cycle II, there were no students who scored below 70 and those who scored 70 were 6 students (25%) and students who scored above 70 were 13 students (75%).